2015
DOI: 10.1007/s00338-015-1335-6
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of coral calcification to extreme temperature variations in the Kimberley region, northwest Australia

Abstract: We report seasonal changes in coral calcification within the highly dynamic intertidal and subtidal zones of Cygnet Bay (16.5°S, 123.0°E) in the Kimberley region of northwest Australia, where the tidal range can reach nearly 8 m and the temperature of nearshore waters ranges seasonally by *9°C from a minimum monthly mean of *22°C to a maximum of over 31°C. Corals growing within the more isolated intertidal sites experienced maximum temperatures of up to *35°C during spring low tides in addition to being routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 67 publications
1
81
1
Order By: Relevance
“…Corals on the reef flat of the Kimberley region have to cope with extended aerial exposure during spring low tides (up to several hours, Figure 2) and periods of stagnant water alternating with strong tidal currents (>10 knots). These physical conditions create extreme fluctuations in environmental parameters, such as temperature (e.g., the well-studied Shell Island where temperature can fluctuate by up to 7 • C daily, Dandan et al, 2015;Schoepf et al, 2015), pH (e.g., Tallon Island where pH can fluctuate from 7.6 to 8.8 units over a spring low tide, Pedersen et al, 2016), dissolved oxygen (Pedersen et al, 2016;Gruber et al, 2017), unusually turbid waters, and monthly SST exceeding 30 • C for several months a year. Despite these extreme conditions, highly diverse coral reefs exist throughout the Kimberley of up to 225 species (Rosser and Veron, 2011;Richards et al, 2015), which are comparable to inshore reefs in the central GBR ∼2 decades ago (Richards et al, 2015).…”
Section: Macrotidal Coral Reef Environmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Corals on the reef flat of the Kimberley region have to cope with extended aerial exposure during spring low tides (up to several hours, Figure 2) and periods of stagnant water alternating with strong tidal currents (>10 knots). These physical conditions create extreme fluctuations in environmental parameters, such as temperature (e.g., the well-studied Shell Island where temperature can fluctuate by up to 7 • C daily, Dandan et al, 2015;Schoepf et al, 2015), pH (e.g., Tallon Island where pH can fluctuate from 7.6 to 8.8 units over a spring low tide, Pedersen et al, 2016), dissolved oxygen (Pedersen et al, 2016;Gruber et al, 2017), unusually turbid waters, and monthly SST exceeding 30 • C for several months a year. Despite these extreme conditions, highly diverse coral reefs exist throughout the Kimberley of up to 225 species (Rosser and Veron, 2011;Richards et al, 2015), which are comparable to inshore reefs in the central GBR ∼2 decades ago (Richards et al, 2015).…”
Section: Macrotidal Coral Reef Environmentsmentioning
confidence: 99%
“…Furthermore, a seasonal calcification study revealed high resilience of coral calcification to both intertidal and subtidal temperature conditions as branching and massive corals calcified at rates that were comparable to those of similar species at a more typical coral reef 1,200 km to the southwest (Ningaloo Reef; Dandan et al, 2015). Given that rising sea levels are expected to reduce extreme temperature variation on macrotidal reef flats such as Tallon Island (Lowe et al, 2016), reef flat communities might have more time than other reef types to acclimatize and/or adapt to ongoing ocean warming.…”
Section: Macrotidal Coral Reef Environmentsmentioning
confidence: 99%
See 3 more Smart Citations